2010
DOI: 10.1089/vbz.2009.0079
|View full text |Cite
|
Sign up to set email alerts
|

Raccoon (Procyon lotor) Movements and Dispersal Associated with Ridges and Valleys of Pennsylvania: Implications for Rabies Management

Abstract: The raccoon (Procyon lotor) continues to be a prominent terrestrial rabies reservoir in the eastern United States. Describing the dispersal and movements of these animals and determining geographic features that are natural hindrances or corridors to movements could be used to assist oral rabies vaccination efforts. The landscape of the ridge-and-valley system in Pennsylvania exhibits characteristics of both natural potential hindrances and travel corridors to the movements of wildlife. The movements of 49 rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…However, raccoons might also inhabit suboptimal habitats at lower densities. It is important to know the drivers of raccoon invasions, the potential habitats, as well as the barriers for their expansion [22] to predict further changes in their distribution and to delineate focal areas for high-priority management.…”
Section: Introductionmentioning
confidence: 99%
“…However, raccoons might also inhabit suboptimal habitats at lower densities. It is important to know the drivers of raccoon invasions, the potential habitats, as well as the barriers for their expansion [22] to predict further changes in their distribution and to delineate focal areas for high-priority management.…”
Section: Introductionmentioning
confidence: 99%
“…Landscape and habitat: Landscape and habitat can have a range of impacts on the efficacy of vaccination regimes. Together they result in heterogeneous distributions, densities and dispersal movements/contacts of wild vertebrate species that result in spatially variable uptake of baits (Beasley et al, ; Olson & Werner, ; Puskas et al, ; Reynolds, Hirsch, Gehrt, & Craft, ). If this is not taken into account in the design of vaccination campaigns, reduced efficacy or simply failure may result (Sillero‐Zubiri et al, ).…”
Section: Ecological Considerations In Designing and Implementing Campmentioning
confidence: 99%
“…One hypothesis is that this may be due to the high ridges to the west acting as a physical barrier to raccoon (and virus) movement, 28,29 although studies examining this hypothesis have been equivocal. 30,31 To our knowledge, this is only the second ecological study to examine RRV in WV with an eye toward possible predictors, and clustering, of cases. The prior study indicated that rurality, as derived from the UIC, and percentage of agricultural land use were the only factors significantly predictive of RRV infection, with cases increasing as agricultural land use increased and as counties became less rural.…”
Section: Discussionmentioning
confidence: 99%
“…30 Interestingly, the same investigators, using telemetry on individual raccoons in the same area, indicated that there was little evidence of animals crossing the ridge and suggested that the spur valleys that tended to run perpendicular to the ridge acted as corridors for raccoon movement. 31 They addressed the seeming contradiction between the two studies by pointing out that they had effectively three populations in their study, one on the ridgetop and one in each of the adjacent valleys, and while their study provided little evidence of contact between the valleys, there was contact by animals from each valley with the ridgetop population. 31 As such, the ridgetop animals acted as a conduit for exchange of genetic material between the valleys.…”
Section: Factors Associated With Spread Of Rrvmentioning
confidence: 99%
See 1 more Smart Citation